2009
DOI: 10.1111/j.1754-9485.2009.02053.x
|View full text |Cite
|
Sign up to set email alerts
|

Radioresistant malignant myoepithelioma of the breast with high level of ataxia telangiectasia mutated protein

Abstract: Malignant myoepithelioma of the breast (MMB) is a rare and often aggressive disease with poor prognosis. Little is known regarding its optimal treatment and progression. We describe the clinical history of a woman following excision of a benign adenomyoepithelioma which recurred years later as a radioresistant malignant myoepithelioma with high levels of ataxia telangiectasia mutated protein and mutant p53 (Cys135Phe). MMB requires close follow-up and aggressive treatment. If adjuvant radiotherapy is adopted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Another case report described recurrent AME (a fourth recurrence after excisional biopsy, repeat excisional biopsy, and mastectomy) treated with 60 Gy RT to the chest wall, resulting in 15 months of local control but then later progressing to develop lung metastasis [4]. Case reports of malignant AME have utilized RT (50 Gy in 25 fractions followed by a 9 Gy in three fraction boost) where, despite mastectomy, there was tumor progression [10]. Adjuvant RT was employed in our patient to achieve local control in the setting of AME with a lymph nodes metastasis after resection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another case report described recurrent AME (a fourth recurrence after excisional biopsy, repeat excisional biopsy, and mastectomy) treated with 60 Gy RT to the chest wall, resulting in 15 months of local control but then later progressing to develop lung metastasis [4]. Case reports of malignant AME have utilized RT (50 Gy in 25 fractions followed by a 9 Gy in three fraction boost) where, despite mastectomy, there was tumor progression [10]. Adjuvant RT was employed in our patient to achieve local control in the setting of AME with a lymph nodes metastasis after resection.…”
Section: Discussionmentioning
confidence: 99%
“…A link between upregulation of ATM protein in malignant AME and possible radioresistance has been reported [10]. Proponents of RT have advocated that if RT is to be employed, minimal postoperative delays, higher doses, and accelerated fractionation should be considered [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Axillary lymph node dissection is not indicated for these lesions unless there is clinically detected lymphadenopathy because metastasis to nodes is unusual 14. There is little objective evidence to support a role for radiotherapy107 or chemotherapy in the management of AME.…”
Section: Clinical Behaviourmentioning
confidence: 99%
“…A clinical study from the Peking University of China [24] gave similar results, with eight out of 12 patients developing a recurrence after postoperative radiotherapy. Fang et al found that high levels of ataxia telangiectasia-mutated protein (ATM) might induce radioresistance in MC, and recommended that an accelerated, high-dose approach should be delivered as soon as possible after surgery [31]. We believe that changing the fraction of radiation or using high-liner energy transmission (LET) radiotherapy, such as carbon particles and fast neutrons, may help to improve outcome.…”
Section: Discussionmentioning
confidence: 92%